Electronic media and information technology - Sudhir, S.N (Pearl Books, 2020)
Electronic media is the media that one can share on any electronic device for the audiences viewing unlike static media (Printing) electronic media is broadcasted to the wider community. Examples of Electronic media are things such as the television, the radio or the wide internet. Computers can now display film-style video clips and streaming media, encouraged by increased processor speed, storage capacity, and broadband access to the Internet. General-purpose computing hardware can now be used to capture, store, edit, and transmit television and movie content, as opposed to older dedicated analog technologies. Nowadays, the computer has become pervasive in scientific communication. It has played an important supportive part in the communication process since scientific tests have been written using word processors, rather than typewriters, so that they are immediately available in digital form. In that form, they can be stored electronically and either consulted on the screen or printed on paper. With the advent of networking technology, electronic media have started to play a leading part in communication processes: the electronic transmission of messages. This book portrays some salient features of electronic media, which are highly useful and informative to students and professionals in the field. Definitely it will serve the purpose of all those for whom it is meant.